Adelante Mujer Hispana Conference 1997 - Adelante Mujer Hispana::::::::::::::: (2024)
Program for the Adelante Mujer Hispana Conference. Held on Sunday, March 15, 1997 at San Jose State University. The Mistress of Ceremonies was Betty Martinez (Conference Coordinator). The conference included a Keynote Address by Cecilia Burciaga (Executive Assistant to the President and Director of Long Range Planning, California State University, Monterey Bay), and Career